A structural model of total quality management, kaizen, operational performance on service quality and patient satisfaction - Abadi, Indra; Haming, Murdifin; S., Baharuddin; Mahmud, Amir (Archives of Business Research, 2018)
Tests are the strength effect of total quality management (TQM), Kaizen and operational performance on service quality and patient satisfaction. The other part we will test is the service quality as a mediation role to explain the effect of total quality management (TQM), Kaizen and operational performance on patient satisfaction. This research was conducted in the city of Makassar with the entire population is a patient. By using the formula Slovin, found a sample of 398 respondents. Inferential statistical analysis was used to test the hypothesis of the research is Structural Equation Modeling (SEM). The results of this study indicate that TQM, Kaizen and operational performance have been shown to contribute significantly positively on service quality and patient satisfaction. The role of service quality is proven to be a mediating variable in analyzing TQM, Kaizen and operational performance effect on patient satisfaction.